2022
DOI: 10.1111/ijn.13123
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a psychoeducational intervention on health outcomes of patients undergoing haemodialysis: A randomized controlled trial

Abstract: Aim The aim of this work is to examine the effectiveness of a psychoeducational intervention on self‐efficacy (primary outcome), anxiety, depression, treatment adherence, and health‐related quality of life (HRQoL) of patients undergoing haemodialysis. Methods A two‐group randomized controlled trial of 124 patients (65 and 59 patients in the intervention and control groups, respectively) recruited from a tertiary hospital in Singapore was conducted. Data were collected from January 2015 to June 2016. Outcomes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 51 publications
0
15
1
Order By: Relevance
“…In terms of allocation concealment, two studies [ 36 , 37 ] provided no information and were assessed as unclear. The baseline of most of the 14 studies was homogeneous, but three out of 14 studies [ 18 , 38 , 39 ] found some baseline imbalance (e.g., in health information teaching clinic attendance, HADS-depression score and effects of kidney disease on daily [18] , and in PHQ9 score [38] , and in stress and depression score [39] ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In terms of allocation concealment, two studies [ 36 , 37 ] provided no information and were assessed as unclear. The baseline of most of the 14 studies was homogeneous, but three out of 14 studies [ 18 , 38 , 39 ] found some baseline imbalance (e.g., in health information teaching clinic attendance, HADS-depression score and effects of kidney disease on daily [18] , and in PHQ9 score [38] , and in stress and depression score [39] ).…”
Section: Resultsmentioning
confidence: 99%
“…One study [40] blinded participants of the treatment assignments using attention placebo control. In 5 studies [ 18 , 39 , 41 43 ], the outcome assessors were blinded. In most of the studies, the same treatment was used in both groups, except for the intervention.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations